Karkas Ayam Broiler Yang Diberi Umbi Amorphophallus companulatus: Carcass Of Broiler Chickens Fed with Amorphophallus companulatus - Theresia Nur Indah Koni; Tri Anggarini Yuniwaty Foenay; Hieronymus Yohanes Chrysostomus (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2021)
Abstract Amorphophallus companulatus (AC) is a plant from the Araceae family that contains high metabolizable energy and an alternative feedstuff for livestock. This study aimed to investigate the effect of feeding diet containing AC on slaughter weight, carcass weight, and abdominal fat of broiler chickens. The feeding trial lasted for 35 days. For the sample, 112 broiler chicks, all a day old (DOC) were used. The research had 4 treatment groups and 4 replications with 7 birds per replication. The four treatments were P0 (Control ration without AC); P1 (rations containing 5% of AC); P2 (rations containing 10% of AC); P3 (rations containing 15% AC). Slaughter weight, carcass weight, and abdominal fat weight data were analyzed by variance analysis and followed by Duncan's multiple range test with a confidence level of 0.05. The addition of AC tubers affected the slaughter weight, carcass weight, and abdominal fat weight of broiler chickens. The slaughter and carcass weight in chickens fed with the control ration was significantly (P <0.05) higher than the chicken fed with rations containing AC. The abdominal fat weight was significantly (P <0.05) higher in chickens fed with control rations compared to those fed with AC rations. In conclusion, AC tuber meal in the ration can reduce the slaughter weight, carcass weight, and abdominal fat weight of broiler chickens. Keywords: Abdominal fat; Amorphophallus companulatus; Broiler; Carcass weight; Final body weight. Abstrak Amorphophallus companulatus (AC) merupakan Araceae yang mengandung energi metabolisme yang tinggi dan sebagai bahan pakan alternatif bagi ternak. Penelitian ini bertujuan untuk mengkaji pengaruh penggunaan AC dalam ransum terhadap bobot potong, berat karkas, dan lemak abdominal ayam broiler. Penelitian ini dilakukan selama 35 hari. Seratus dua belas ekor ayam broiler umur sehari digunakan dalam penelitian. Ada 4 kelompok perlakuan dengan 4 ulangan masing-masing 7 ekor ayam per ulangan. Keempat perlakuan tersebut adalah P0 (Ransum kontrol tanpa AC); P1(ransum yang mengandung 5% AC); P2 (ransum yang mengandung 10% AC); P3 (ransum yang mengandung 15% AC). Data berat potong, berat karkas dan berat lemak abdominal dianalisis dengan analisis varians dan dilanjutkan dengan uji jarak berganda Duncan pada tingkat kepercayaan 0,05. Pemberian umbi AC berpengaruh terhadap berat badan akhir, berat karkas dan berat lemak abdominal ayam broiler. Berat badan akhir, berat karkas pada ayam yang diberi ransum kontrol secara nyata (P <0,05) lebih tinggi daripada ayam yang diberi ransum mengandung AC. Bobot lemak abdominal secara nyata (P<0,05) lebih tinggi pada ayam yang diberi ransum kontrol dibandingkan yang diberi ransum AC. Kesimpulannya, tepung umbi AC dalam ransum dapat mengurangi berat badan akhir, berat karkas dan lemak abdominal ayam broiler. Kata kunci: Lemak abdominal; Amorphophallus companulatus; Broiler; Berat karkas; Berat badan akhir.